Micro/Nano Electrode Array Sensors: Advances in Fabrication and Emerging Applications in Bioanalysis - Liu, Yang; Li, Xiuting; Chen, Jie; Yuan, Chonglin (Frontiers in Chemistry, 2020)
Due to the rapid development of micro/nano manufacturing techniques and the greater understanding in electrochemical principles and methods, micro/nano electrode array sensing has received much attention in recent years, especially in bioanalysis. This review aims to explore recent progress in innovative techniques for the construction of micro/nano electrode array sensor and the unique applications of various types of micro/nano electrode array sensors in biochemical analysis. Moreover, the new area of smart sensing benefited from miniaturization of portable micro/nano electrode array sensors as well as wearable intelligent devices are further discussed.